Acid Isolation Techniques for Silica isolation from Rice Husk and Determination of Its Physicochemical Properties - Siti Mutrofin; Leo Krisna; Diah Mardiana; Rachmat Triandi T (Chemistry Department, The University of Brawijaya, 2022)
Previous research showed that rice husk has a high silica content so it becomes an alternative for processing rice waste. The acid leaching method is a technique to isolate silica by adding an acid solution. The research aim is to obtain the optimum silica yield and determine the chemical ash content of rice husks (rice IR-64,). Rice husks were first calcined at two various temperatures and times. The average yields obtained were 19.54% (500oC / 1 hr), 18.42% (500oC / 2 hrs), 25.03% (700oC /1 hr), and 22.4% (700oC/2 hrs). The physical appearance of ash was grains and white (700 oC/1hr), that were rinsed with 1 M HCl solution to remove impurities. Added 1 M NaOH was to form sodium silicate. The last step was to isolate silica using different concentrations of HCl and HNO3 (3 M, 2 M, and 1 M). The highest result was 99.87% of silica under HNO3 1 M solution. An infrared study supports that the isolated product was silica, with the presence of prominent peaks at 1102 cm-1 (stretching Si-O) and 471 cm-1 (bending Si-O). A unique peak at 958 cm-1 for Si-O-Ca present at the isolated silica using HCl 3 M, gives information on inosilicate type structure. X-ray diffraction analysis with QualX application showed that silica had cristobalite and wollastonite peaks, and the value of crystallinity index was about 63.91%.